Genetic and technological diversity of Streptococcus thermophilus isolated from the Saint-Nectaire PDO cheese-producing area - Grizon, Anna; Theil, Sebastien; Callon, Cecile; Gerber, Pauline; Helinck, Sandra; Dugat-Bony, Eric; Bonnarme, Pascal; Chassard, Christophe (Frontiers in Microbiology, 2023)
Streptococcus thermophilus is of major importance for cheese manufacturing to ensure rapid acidification, however, studies indicate that intensive use of commercial strains lead to the loss of typical characteristics of the products. To strengthen the link between the product and its geographical area and improve the sensory qualities of cheeses, cheese-producing PDO are increasingly interested in the development of specific autochthonous starter cultures. The present study is therefore investigating the genetic and functional diversity of Streptococcus thermophilus strains isolated from a local cheese-producing PDO area. Putative Streptococcus thermophilus isolates were isolated and identified from milk collected on the Saint-Nectaire cheese-producing PDO area and from commercial starters. Whole genomes of isolates were sequenced and a comparative analysis based on their pangenome was carried out. Important functional properties were studied, including acidifying and proteolytic activities. Twenty-two isolates representative of the diversity of the geographical area and four commercial strains were selected for comparison. The resulting phylogenetic trees does not correspond to the geographic distribution of isolates. The clustering based on the pan-genome analysis indicates that isolates are divided into 5 distinct groups. A KEGG functional annotation of the accessory genes indicates that the accessory genes content of isolates are involved in different functional categories. High variability in acidifying activities and little diversity in proteolytic activities were also observed. These results indicate that high genetic and functional variabilities of the species Streptococcus thermophilus may arise from a small (1800 km 2 ) geographical area, and may be exploited to meet demand for use as autochthonous starters.